Peran Efek Antioksidan Pada Naringenin Sebagai Anti Diabetes: Literature Review - Putriliana, Salma Chesa; Atmaka, Dominikus Raditya; Farapti, Farapti (Jurnal Gizi Ilmiah, 2025)
Diabetes mellitus is becoming one of the major problems in the world that causes a few cases of other diseases. This disease is characterized by hyperglycaemia which occurs disrupted secretion or insulin function or both. Oxidative stress, caused by an imbalance between Reactive Oxygen Species (ROS) and antioxidants, can be one of the causes of complications of the disease. Naringenin is potentially found to be an antidiabetic by various mechanisms. The literature research was carried out through articles over the past ten years aimed at finding out how the antioxidant effect mechanisms of naringenin against diabetes mellitus. Research results show that naringenin has significant potential as a therapeutic agent in managing diabetes mellitus through reduce inflammation, increased antioxidants mechanism as well as improved insulin functions and glucose metabolism.